Management of Anxiety Using Autogenic Relaxation in Preoperative Cataract Patients - Sofiah Nurlita; Dewi Siyamti (International Forum of Researchers and Lecturers, 2026)
Cataracts are a leading cause of visual impairment requiring surgical intervention. Preoperative conditions can trigger psychological responses of anxiety in patients. Untreated anxiety can affect hemodynamic stability and the success of medical procedures. Autogenic relaxation is a non-pharmacological intervention that can reduce anxiety by using self-suggestion to achieve a relaxed state in patients. This study aims to describe the management of nursing care in anxiety reduction using autogenic relaxation therapy in pre-cataract surgery patients. This research method used a case study design with a comprehensive nursing care approach including assessment, data analysis, intervention, implementation, and evaluation. The patient's anxiety level was measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Nursing implementation was carried out over 5 hours with structured autogenic relaxation therapy interventions delivered before the patient underwent surgery. The final outcome of this case management was a reduction in the patient's anxiety. Based on the evaluation of the nursing actions taken, it can be concluded that the anxiety problem in pre-cataract surgery patients was resolved. Autogenic relaxation has been shown to reduce anxiety in pre-cataract surgery patients. It is hoped that this intervention can be implemented as a safe and efficient standard of independent nursing care in pre-operative patient psychological preparation.